Give & Take : 1 Exhibition 2 Sites. - Borg, Alan; Corrin, Lisa; Haacke, Hans; Peyton-Jones, Julia (London : Serpentine Gallery, 2001)
Aptekar, Ken ; Xu Bing ; Cummings, Neil ; Lewandowska, Marysia ; Delvoye, Wim ; Koons, Jeff ; Lou, Liza ; Paine, Roxy ; Morgan Puett, J. ; Bocanegra, Suzanne ; Quinn, Marc ; Serrano, Andres ; Shonibare, Yinka ; Sugimoto Hiroshi ; Taaffe, Philip ; Haacke, Hans
biog. per kunstenaar
Engels
Give & Take, Serpentine Gallery, London ; Victoria and Albert Museum, London, 30 January - 1 April 2001
boek